History of Nagbanshis in Jharkhand - Archana Sada Suman Tudu, R K; Sarma, Rabindranath (International Journal of Psychosocial Rehabilitation, 2020)
Jharkhand is a state situated in the northeast of India. It came into existence on 15th November 2000 after separation from Bihar. It is bounded by Bihar in the north, Odisha in the South, West Bengal in the east and Madhya Pradesh and Chattisgarh in the south. In ancient times it used to be an entirely forested area. The hills of Kaimur and Vindhya surrounded this region, which was covered in lush woods and hills. Primitive tribes came to dwell here because of the region's abundance of forests and mountains. The ancient tribes that lived here were Asur, Khadiya, and Birhor. Subsequently, the Korba tribe arrived in the Jharkhand region, followed by the Munda, Oraon, Ho, and other tribes. Following these, the tribes such as Chero, Kharwar, Bhumij, and Shanthal made their way to Jharkhand. Nagbansh was the first ruling dynasty that continued to rule till the modern period. The researcher has attempted to go extensively into the history of the Nagbanshi and their interactions with the different tribes residing in Jharkhand.